2020
DOI: 10.3390/ijms21113921
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tissue-Specific Ubiquitin Ligases, RNF183, RNF186, RNF182 and RNF152, in Disease and Biological Function

Abstract: Ubiquitylation plays multiple roles not only in proteasome-mediated protein degradation but also in various other cellular processes including DNA repair, signal transduction, and endocytosis. Ubiquitylation is mediated by ubiquitin ligases, which are predicted to be encoded by more than 600 genes in humans. RING finger (RNF) proteins form the majority of these ubiquitin ligases. It has also been predicted that there are 49 RNF proteins containing transmembrane regions in humans, several of which are specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 71 publications
(162 reference statements)
0
34
0
Order By: Relevance
“…RNF183, RNF182, RNF186, and RNF152, are further identified as the RNF183 family, which share the similar structure RING finger domain (C3HC4) at their N-terminus and transmembrane domains at their C-terminus with high homology (Kaneko et al, 2016;Okamoto et al, 2020a). As common features, members of RNF183 family have exhibited a broad range of functions in diverse biological and pathological processes such as prolonged endoplasmic reticulum stress, apoptosis, ischemia-reperfusion injury, oxygen, and glucose metabolism, immune and inflammatory response (Liu et al, 2008;Nectoux et al, 2010;Wang et al, 2018;Wu et al, 2018;Cao et al, 2019;Maeoka et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…RNF183, RNF182, RNF186, and RNF152, are further identified as the RNF183 family, which share the similar structure RING finger domain (C3HC4) at their N-terminus and transmembrane domains at their C-terminus with high homology (Kaneko et al, 2016;Okamoto et al, 2020a). As common features, members of RNF183 family have exhibited a broad range of functions in diverse biological and pathological processes such as prolonged endoplasmic reticulum stress, apoptosis, ischemia-reperfusion injury, oxygen, and glucose metabolism, immune and inflammatory response (Liu et al, 2008;Nectoux et al, 2010;Wang et al, 2018;Wu et al, 2018;Cao et al, 2019;Maeoka et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…In sable, fatty acids are uniformly mobilized from anatomically distinct fat deposits (Nieminen and Mustonen 2007), whereby the fatty acid metabolism is regulated by positively selected genes of the ACSL family, maintaining a low body fat content of ~8% (Zhao et al 2019). In our analyses we did not detect changes in the ACSL gene family, but we observed duplications of ASB6, SLC25A10, RNF186 and BORCS6, which have been implicated in effective regulation of fat storage usage and response to nutrient availability (Wilcox et al 2004;Mizuarai et al 2005;Schweitzer et al 2015;Okamoto et al 2020). Moreover, partial deletions of APOD, PDHB, LDLR, and CERS5, associated with lipid metabolic processes (Carmo et al 2009;Serão et al 2011;Tavori et al 2015;Gosejacob et al 2016), indicate a possible association with adaptive fasting and energy conservation.…”
Section: Resource Availability In the Northern Palaearctic: Wolverine And Sablementioning
confidence: 55%
“…The abnormal expression of RNF183 is thought to be involved in several diseases, not only tumorigenesis but also inflammatory conditions such as inflammatory bowel disease (IBD). The molecular mechanism underlying the development and pathophysiology of this disease has not yet been fully elucidated (Yu et al, 2016;Okamoto et al, 2020). Although only a few studies on the role of RNFs have been reported in fish, it is clear that RNF is a regulator of downstream gene expression and molecular pathways (Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%